2018
DOI: 10.1111/andr.12476
|View full text |Cite
|
Sign up to set email alerts
|

The SET protein promotes androgen production in testicular Leydig cells

Abstract: SummaryApproximately 40% of middle‐aged men exhibit symptoms of late‐onset hypogonadism (LOH). However, the mechanism of androgen deficiency is still currently unclear. As shown in our previous studies, the SET protein is expressed in testicular Leydig cells and ovarian granule cells. This study was designed to investigate the effect of the SET protein on androgen production in Leydig cells. The AdCMV/SET and AdH1siRNA/SET adenoviruses were individually transduced into a cultured mouse Leydig cell line (mLTC‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the present study, MLTC-1 mouse Leydig cell line was used to study the role of BMI1 in steroidogenesis, due to stable and persistent production of testosterone by this type of cell [ 35 37 ]. By using small-molecule BMI1 specific inhibitor PTC-209 [ 38 , 39 ], we observed a drastic loss of BMI1 in MLTC-1 cells ( Figure 2(a ,b)).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, MLTC-1 mouse Leydig cell line was used to study the role of BMI1 in steroidogenesis, due to stable and persistent production of testosterone by this type of cell [ 35 37 ]. By using small-molecule BMI1 specific inhibitor PTC-209 [ 38 , 39 ], we observed a drastic loss of BMI1 in MLTC-1 cells ( Figure 2(a ,b)).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study showed that SET protein was highly expressed in mouse Leydig cells [10]. A subsequent study showed that SET overexpression or knockdown could significantly promote or decrease testosterone production [11]. These results confirmed the relationship between SET and testosterone production in Leydig cells.…”
Section: Introductionmentioning
confidence: 58%
“…SET is reported to be a phosphorylated protein that is ubiquitously expressed in various tissues, particularly in steroidogenic cells within the adrenal gland and gonad, suggesting that it may be closely assiciated with steroidogenesis [19,20]. Previous work has shown that human chorionic gonadotropin (hCG) increased SET mRNA and protein expression through the cAMP/PKA signaling pathway to stimulate steroidogenic enzyme expression, which then promotes testosterone production in Leydig cells [11]. In the present study, we found that YC could paly a similar role to hCG in upregulating the expression of SET, StAR, P450scc, and HSD17B to stimulate steroidogenesis in Leydig cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Leydig cells stimulate spermatogenesis by secreting testosterone, a steroid hormone, which creates an environment that supports proper spermatogenesis development (Bing Chen et al, 2010; Sharpe et al, 1990). The synthesis and secretion of the testosterone is controlled by a network of intracellular and extracellular factors (Zhang et al, 2018). For example, a nuclear SE translocation (SET) protein is believed to promote steroidogenesis in Leydig cells (Dai et al, 2014; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and secretion of the testosterone is controlled by a network of intracellular and extracellular factors (Zhang et al, 2018). For example, a nuclear SE translocation (SET) protein is believed to promote steroidogenesis in Leydig cells (Dai et al, 2014; Zhang et al, 2018). Still, many details on the function and regulation of Leydig cells remain unknown (Zirkin & Papadopoulos, 2018).…”
Section: Discussionmentioning
confidence: 99%